THE EFFECT OF GREEN ACCOUNTING AND INTELLECTUAL CAPITAL ON FIRM VALUE WITH ENTERPRISE RISK MANAGEMENT AS A MODERATING VARIABLE - Ni Putu Sri Yuni Enjelika; I Gusti Ayu Nyoman Budiasih (CV. Adiba Aisha Amira, 2025)
This study aims to empirically examine the effect of green accounting and intellectual capital on firm value with Enterprise Risk Management as a moderating variable. The theoretical foundation of this research is the signaling theory and legitimacy theory. The research method employs a quantitative associative approach using secondary data from the financial reports of energy sector companies listed on the Indonesia Stock Exchange for the period 2021–2023. The research sample was selected using a purposive sampling method, resulting in 170 observations. The results show that green accounting has no effect on firm value, while intellectual capital has a positive effect on firm value. Furthermore, Enterprise Risk Management does not moderate the effect of green accounting and intellectual capital on firm value. These findings indicate that green accounting information has not been fully considered by investors, intellectual capital is a strategic asset essential for company sustainability, and Enterprise Risk Management has not been optimally integrated with sustainability practices and intellectual management in the context of this study